Polyhydroxyester Films Obtained by Non-Catalyzed Melt-Polycondensation of Natural Occurring Fatty Polyhydroxyacids - Benítez, José Jesús; Heredia-Guerrero, José Alejandro; Guzmán-Puyol, Susana; Barthel, Markus J.; Domínguez, Eva; Heredia, Antonio (Frontiers in Materials, 2015)
Free-standing polyesters films from mono and polyhydroxylated fatty acids (C16 and C18) have been obtained by non-catalyzed melt-condensation polymerization in air at 150°C. Chemical characterization by Fourier Transform Infrared Spectroscopy (FTIR) and 13C Magic Angle Spinning Nuclear Magnetic Resonance (13C MAS-NMR) has confirmed the formation of the corresponding esters and the occurrence of hydroxyl partial oxidation which extent depends on the type of hydroxylation of the monomer (primary or secondary). Generally, polyester films obtained are hydrophobic, insoluble in common solvents, amorphous and infusible as revealed by X-ray Diffraction (XRD) and Differential Scanning Calorimetry (DSC). In -polyhydroxy acids, esterification reaction with primary hydroxyls is preferential and, therefore, the structure can be defined as linear with variable branching depending on the amount of esterified secondary hydroxyls. The occurrence side oxidative reactions like the diol cleavage are responsible for chain cross-linking. Films are thermally stable up to 200-250°C though this limit can be extended up to 300°C in the absence of ester bonds involving secondary hydroxyls. By analogy with natural occurring fatty polyesters (i.e. cutin in higher plants) these polymers are proposed as biodegradable and non-toxic barrier films or coatings to be used, for instance, in food packing